Management Optimization of Cipanunjang-Cileunca Reservoir in Bandung Regency Using Discrete Markov Methods - Mariana Marselina; Arwin Sabar; Iin Pratama Sari (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2018)
This research discusses about intake Cikalong as water resource infrastructure supplying water for PDAM Bandung City and PDAM Bandung Regency that depend on the operational of Cipanunjang Dam-Cileunca Dam, Plengan Hydropower, Lamajan Hydropower, Cikalong Hydropower and water from Cisangkuy River. Nowdays, capacity of PDAM Bandung city is 1800 L/sec and capacity of PDAM Bandung Regency is 500 L/sec. However, the amount of water that could be provided by PDAM Bandung City is 1400 L/sec while PDAM Bandung Regency is 200 L/sec. Aim: Optimization on upstream infrastructure is needed to make sure the quantity of water being supplied sufficient. Methodology and Result: There are some methods that can be used to fulfill that aim, on this research use Stochastic Markov Method. The optimization of the reservoir is achieved by the condition of the guideline track and the actual trajectory approaching 1, which means the absence of wasted water through the spillway but through the reservoir utility function for turbine demand, irrigation raw water and raw drinking water in the downstream. The comparison between trajectory and actual trajectory of Cipanunjang Reservoir is 0.861 while for optimization of Cileunca Reservoir is 0.827. Conclusion, significance and impact study: The correlation between the actual (historical) discharge and the Markov estimation discharge on the Cipanunjang-Cileunca Reservoir is closed to 1, so it can be show that the discharge estimation is conceptual because it corresponds to the actual condition (actual discharge).